Natural theology - Vos, Geerhardus (Reformation Heritage Books, 2022)
"Biblical and natural theology may not appear to mix but the two do actually belong together. Vos's reputation as the father of contemporary biblical theology is not negated by his earlier teaching of natural theology - appearing here for the first time in English. Gathered from source material found in the Heritage Hall archives at Calvin Seminary and University, these are the earliest notes of Vos's lectures on natural theology. They demonstrate his understanding of Reformed orthodox approaches as well as extensive knowledge of contemporary developments in the subject. Given that his Reformed Dogmatics lacks a prolegomenon, and that this work discusses religion and the proofs of the existence of God, this content could be regarded, and may have formed, Vos's introduction to dogmatics. "--